In vitro testing strategy for nanomaterials including database (Deliverable 5): final report - Norppa, Hannu (2014)
WP5 had two objectives: - To generate in vitro genotoxicity data on manufactured MNs (specific objective #3). - To perform a round robin test on in vitro genotoxicity testing of MNs (specific objective #4) WP5 addressed the basic questions of in vitro genotoxicity testing of manufactured nanomaterials (MNs): how well in vitro assays can be used for revealing the genotoxic potential of MNs, which assays are suitable for this task, and which modifications are needed in standard tests when MNs are studied. WP5 aimed at establishing robust methodology to screen the in vitro genotoxicity of MNs in pulmonary, oral, and epidermal cell systems. These assays were to be applied to all MNs included in the project. On the basis of the results obtained, a ring test was to be performed using the most promising approach. Finally, the results were to be evaluated for correlation with in vivo results and used, together with other genotoxicity data available and the kinetic results, to formulate a strategy for genotoxicity testing of MNs (this deliverable).